Fingerprints of Both Watson–Crick and Hoogsteen Isomers of the Isolated (Cytosine-Guanine)H + Pair - Cruz Ortiz, Andres Felipe (2017)
Gas phase protonated guanine-cytosine (CGH+) pair was generated using an electrospray ionization source from solutions at two different pH (5.8 and 3.2). Consistent evidence from MS/MS fragmentation patterns and differential ion mobility spectra (DIMS) point toward the presence of two isomers of the CGH+ pair, whose relative populations depend strongly on the pH of the solution. Gas phase infrared multiphoton dissociation (IRMPD) spectroscopy in the 900-1900 cm-1 spectral range further confirms that the Watson-Crick isomer is preferentially produced (91%) at pH = 5.8, while the Hoogsteen isomer predominates (66%) at pH = 3.2). These fingerprint signatures are expected to be useful for the development of new analytical methodologies and to trigger isomer selective photochemical studies of protonated DNA base pairs.